A Comparative Study on Knowledge of Euphemism Between Two Generations of the Bidayuh Biatah of Sarawak - Angelia Marjorie / AM, Fabian (Faculty of Education, Language and Communication, UNIMAS, 2025)
Euphemism is a linguistic phenomenon often intrinsically linked with culture, reflecting or mirroring the values and norms of a particular language speaker’s community. This study addresses the insufficient research on euphemisms, particularly among the Bidayuh Biatah speakers. Additionally, there is a linguistic variation between the older and younger generations within the Bidayuh Biatah community, with older speakers often seen as preservers of their language, while the younger speakers are described as speakers of ‘youth language’. This study aimed to analyse euphemisms and compare the Bidayuh Biatah euphemism phenomenon among younger and older generations, highlighting aspects, strategies, and functions as well as the speakers’ understanding of the cultural influences on Bidayuh Biatah euphemisms to a certain extent. The research employed an ethnographic research design, comprising qualitative approach. The qualitative approach involved collecting data through open-ended, in-depth interviews with 16 informants from Kampung Quop: eight older and eight younger speakers, selected based on specific criteria. A word list based on Allan and Burridge (1991) was created as a guide to elicit euphemism in Bidayuh Biatah from the informants. The conceptual framework of this study includes the nine aspects of euphemism as per Allan and Burridge (1991), euphemism strategies in Warren’s Model as suggested by Yetkiner (2006), and the functions of euphemisms outlined by Burridge (2012). The study found that the younger speakers use all nine aspects of euphemism, while the older speakers used eight, excluding referrals of gods. In terms of the strategies, the older generation employed strategies like phonemic replacement and vague reduplication, which were not used by the younger speakers. Conversely, younger speakers used strategies such as borrowing from Malay, which the older speakers did not use. Nevertheless, circumlocution is a common strategy and was often used by both generations. In terms of the euphemism functions based on Burridge (2012), this study revealed the presence of protective, underhand, uplifting, cohesive, and ludic euphemisms, excluding provocative euphemism. These functions reflected the Bidayuh Biatah cultural beliefs and practices through the euphemisms and their functions. Each of the existing euphemism functions provides insight into the complex relationships between cultural influences and euphemistic language use in daily communication among the Bidayuh Biatah community.